Evaluation of a novel Aspergillus IgG lateral flow assay for the diagnosis of non-neutropenic patients with acute and subacute invasive aspergillosis - Yajie Lu; Huanhuan Zhong; Huanhuan Zhong; Yujie Wang; Chao Sun; Yuanyuan Li; Yuchen Cai; Xiaomin Cai; Jiamei Wang; Jinjin Zhong; Xin Su (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeThis study aimed to assess a novel lateral flow assay (LFA) for Aspergillus IgG detection in patients with non-neutropenic invasive aspergillosis (IA).MethodsAspergillus IgG LFA and enzyme-linked immunosorbent assay (ELISA) were performed in non-neutropenic IA patients and control group (proven community acquired pneumonia and healthy persons), respectively. The diagnostic performance of Aspergillus IgG LFA for IA was evaluated and compared with ELISA method.Results33 cases of acute IA, 30 cases of subacute IA and 80 controls were enrolled in this study. The level of plasma Aspergillus IgG LFA in the IA group was significantly higher than that in the control group (190.5 AU/mL vs 50.3 AU/mL, P < 0.001). In total, the sensitivity/specificity/PPV/NPV of Aspergillus IgG LFA was 65.1%/97.5%/95.4%/78.0%. The sensitivity and specificity of Aspergillus IgG LFA were equivalent to those of Aspergillus IgG ELISA with a 120 AU/mL cut-off, but exhibited significantly higher specificity (97.5% vs 87.5%, P = 0.021) compared to the ELISA with an 80 AU/mL cut-off. The consistency was strong among the two methods (P < 0.001, Kappa = 0.67/0.68). The sensitivities/specificities/PPVs/NPVs of Aspergillus IgG LFA were 57.6%/97.5%/90.5%/84.8% for patients with acute IA, and 73.3%/97.5%/91.7%/90.7% for patients with subacute IA, respectively. The “any-positive” strategy, which combined Aspergillus IgG LFA with sputum culture and serum galactomannan (GM), had a sensitivity/specificity/PPV/NPV of 81.1%/94.7%/95.6%/78.3%. The sensitivity/specificity/PPV/NPV of bronchoalveolar lavage fluid (BALF) GM was 65.0%/90.0%/92.9%/56.3%. When combined Aspergillus IgG LFA with BALF GM, the figures were 87.5%/85.0%/92.1%/77.3%.ConclusionsCompared to the Aspergillus IgG ELISA, the Aspergillus IgG LFA exhibits comparable or superior diagnostic efficiency in IA patients, while offering a faster and more convenient option for clinical diagnosis. The “any-positive” strategy of combined diagnosis with Aspergillus IgG LFA serves as a valuable supplement to current diagnostic approaches, particularly benefiting patients who cannot tolerate invasive bronchoscopic procedures.